A systematic review of sport-based life skills programs for young people: The quality of design and evaluation methods. Issue 2 (4th March 2022) - Williams, Charlotte; Neil, Rich; Cropley, Brendan; Woodman, Tim; Roberts, Ross
Abstract: Over the past two decades, researchers have reported positive life skills outcomes for young people participating in sport-based life-skills programs. However, to date, there has been a lack of consideration in the literature regarding the quality of the programs designed and the evaluation methods adopted. Therefore, we conducted a systematic review of the life skills literature to: (a) assess the quality of sport-based life skills program design and evaluation methods; and (b) identify characteristics relating to the quality of sport-based life skills programs where authors had evidenced life skills development and transfer. Using the PRISMA guidelines, we searched six databases for relevant research papers and applied inclusion and exclusion criteria to the papers returned, of which 15 papers met the criteria. We conducted two quality assessment exercises (design and evaluation methods) and found three moderate-high quality life skills programs, 11 moderate quality programs, and one low quality program. We present the characteristics (regarding quality) of intervention designs and methods, conclude with recommendations for designing quality sport-based life skills programs, and provide guidelines for researchers to evaluate sport-based life skills programs. Lay summary : Through engaging in sport-based life skills programs, young people can develop transferable skills. However, the quality of these life skills programs is unclear. We assess the quality of the design and evaluation methods of sport-based life skills programs, present the characteristics of moderate-high and moderate quality programs, and offer recommendations for future research and practice. PRACTICAL IMPLICATIONS: The characteristics identified can be used to aid the development of the content, delivery and evaluation methods within future sport-based life skills programs. The quality assessment tool (QATID) that is embedded within this paper can be used by applied researchers to ensure that the design of their life skills interventions is of high quality. By using the QATID and the Mixed Method Appraisal Tool (MMAT) when designing and evaluating sport-based life skills programs, applied researchers can validate better subsequent claims of program effectiveness.